Dealing with feeling: Specific emotion regulation skills predict responses to stress in psychosis. Issue 2 (15th August 2015) - Lincoln, Tania M.; Hartmann, Maike; Köther, Ulf; Moritz, Steffen
Abstract: Elevated negative affect is an established link between minor stressors and psychotic symptoms. Less clear is why people with psychosis fail to regulate distressing emotions effectively. This study tests whether subjective, psychophysiological and symptomatic responses to stress can be predicted by specific emotion regulation (ER) difficulties. Participants with psychotic disorders ( n =35) and healthy controls ( n =28) were assessed for ER-skills at baseline. They were then exposed to a noise versus no stressor on different days, during which self-reported stress responses, state paranoia and skin conductance levels (SCL) were assessed. Participants with psychosis showed a stronger increase in self-reported stress and SCL in response to the stressor than healthy controls. Stronger increases in self-reported stress were predicted by a reduced ability to be aware of and tolerate distressing emotions, whereas increases in SCL were predicted by a reduced ability to be aware of, tolerate, accept and modify them. Although paranoid symptoms were not significantly affected by the stressors, individual variation in paranoid responses was also predicted by a reduced ability to be aware of and tolerate emotions. Differences in stress responses in the samples were no longer significant after controlling for ER skills. Thus, interventions that improve ER-skills could reduce stress-sensitivity in psychosis. Highlights: The study tests whether emotion regulation skills predict stress-responses in psychosis. The psychosis sample showed stronger stress-responses than healthy controls. Subjective stress-responses were predicted by a reduced ability to be aware of and tolerate emotions. Individual variation in increases in skin conductance levels and paranoia in response to stress were predicted by a reduced ability to be aware of, tolerate, accept and modify emotions. Interventions that improve emotion regulation could reduce stress-sensitivity in psychosis.